Tren Penelitian dalam Memahami Konsep Matematika 2015-2025: Bibliometric Review - Nur Kumala Wardani; Wiryanto Wiryanto; Neni Mariana (LP. Ma'arif Janggan Magetan, 2024)
Understanding mathematical concepts is an important foundation in education, which affects students' abilities in various fields of science. This study aims to identify research trends in understanding mathematical concepts from 2015 to 2024 through bibliometric analysis, mapping the main topics, methods, and significant results achieved. Using the Dimensions AI database, we collected and analyzed 450 publications with a descriptive analysis approach. VOSviewer and Microsoft Excel tools are used for collaborative network visualization, keyword analysis, and descriptive statistics. The results of the study show an increase in the number of publications and citations until 2022, with a decrease in 2023 and 2024. The most prolific writer is Nanang Supriadi, but Aan Putra has the greatest impact based on the number of citations. The most influential journal is Education at a Glance. The novelty keyword analysis identified key clusters, including technology use, STEM approaches, global education policy, teacher skills development, and mathematical literacy. In conclusion, this study provides a comprehensive overview of the development of mathematical concept understanding research, highlighting the importance of technology integration, STEM approaches, and teacher professional development to improve the quality of mathematics education in the future.